The use of cerebral monitoring for intraoperative awareness - Castellon-Larios, Karina; Rosero, Byron R.; Niño-de Mejía, María Claudia; Bergese, Sergio D. (Colombian Journal of Anesthesiology, 2016)
Introduction: the bispectral index monitoring system (BIS) was introduced in the United States in 1994 and approved by the FDA in 1996 with the objective of measuring the level of consciousness through an algorithm analysis of the electroencephalogram (EEG) during general anesthesia. This novelty allowed both the surgeon and the anesthesiologist to have a more objective perception of anesthesia depth. The algorithm is based on different EEG parameters, including time, frequency, and spectral wave. This provides a non-dimensional number, which varies from zero to 100; with optimal levels being between 40 and 60. Objectives: Perform an analysis of the advantages and limitations of the anesthetic management with the bispectral index monitoring, specifically for the management and prevention of intraoperative awareness. Methodology: A non-systematic review was made from literature available in PubMed between the years 2001 and 2015, using keywords such as "BIS", "bispectral monitoring", "monitoreo cerebral", "despertar intraoperatorio", "recall" and "intraoperative awareness". Results: A total of 2526 articles were found, from which only the ones containing both bispectral monitoring and intraoperative awareness information were taken into consideration. A total of 68 articles were used for this review. Conclusion: BIS guided anesthesia has documented less immediate postoperative complications such as incidence of postoperative nausea/vomit, pain and delirium. It also prevents intraoperative awareness and its complications.